The Impact of Fintech on Poverty in Indonesia - Dhea Nursyandi; Endrizal Ridwan (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2026)
This study aims to analyze the direct and indirect effects of FinTech on poverty in Indonesia using panel data from 31 provinces for the 2020–2024 period. Poverty (Pov) is measured by the percentage of the population living below the poverty line, and the FinTech Index (IF) was constructed from electronic money data and P2P lending data. To address endogeneity and omitted variables, the